Validity of the heart rate deflection point as a predictor of lactate threshold during running - Vachon, J. A.; Bassett, D. R.; Clarke, S. (Journal of Applied Physiology, 1999)
During an incremental run test, some researchers consistently observe a heart rate (HR) deflection at higher speeds, but others do not. The present study was designed to investigate whether differences in test protocols could explain the discrepancy. Additionally, we sought to determine whether the HR deflection point accurately predicts lactate threshold (LT). Eight trained runners performed four tests each: 1) a treadmill test for maximal O(2) uptake, 2) a Conconi test on a 400-m track with speeds increasing approximately 0.5 km/h every 200 m, 3) a continuous treadmill run with speeds increasing 0.5 km/h every minute, and 4) a continuous LT treadmill test in which 3-min stages were used. All subjects demonstrated an HR deflection on the track, but only one-half of the subjects showed an HR deflection on the treadmill. On the track the shortening of stages with increasing speeds contributed to a loss of linearity in the speed-HR relationship. Additionally, the HR deflection point overestimated the LT when a continuous treadmill LT protocol was used. In conclusion, the HR deflection point was not an accurate predictor of LT in the present study.